3D- ABAQUS Modelling of Prestressed Concrete Hunched Beams with Multi-Openings of Different Shapes (Journal of Engineering, 2023)
A long-span Prestressed Concrete Hunched Beam with Multi-Opening has been developed as an alternative to steel structural elements. The commercial finite element package ABAQUS/CAE version 2019 has been utilized. This article has presented the results of three-dimensional numerical simulations investigating the flexural behaviour of existing experimental work of supported Prestressed Concrete Hunched Beams with multiple openings of varying shapes under static monotonic loads. Insertion openings in such a beam lead to concentrate stresses at the corners of these openings; as a result, extensive cracking would appear. Correlation between numerical models and empirical work has also been discussed regarding load displacement and crack development, and the obtained outcomes demonstrate a good agreement with the experiments. The ratio of ultimate loads and deflection of the beams tested in the investigation to those of numerical models was 0.98 and 0.97, respectively. So, finite element analysis can be regarded as a behaviour-trustworthy technique for simulating the non-linear behaviour of prestressed concrete rafters with multi-openings from the point of view of complexity, hardly, time-keeping, human effort, and cost.